A cost-of-living squeeze? Distributional implications of rising inflation - Causa, Orsetta (OECD Publishing, 2022)
Inflation has quickly and significantly increased in most OECD countries since the end of 2021 and further accelerated after Russia's war of aggression against Ukraine, mostly driven by surging energy and food prices. Certain categories of households are particularly vulnerable, as large parts of their consumption expenditures are devoted to energy and food. Drawing on national micro-based household budget surveys and on CPI data, this paper provides a quantification of the impact of rising prices on households' welfare. Declines in household purchasing power between August 2021 and August 2022 are estimated to range from 3% in Japan to 18% in the Czech Republic. This decline is driven by energy prices in most countries, especially Denmark, Italy, and the United Kingdom, while energy prices play a lesser role in countries where inflation is more broad-based like the Czech Republic and the United States. In all considered countries, inflation weighs relatively more on low than high-income households. Rural households are hit particularly hard, most often more than low-incomes ones, and this is driven by energy price inflation. To cushion vulnerable households from rising inflation, especially from energy prices, these findings call for a careful targeting of income and price support measures, notwithstanding their administrative and logistical complexity, taking into account their effects on economic activity, inflation, and, last but not least, environmental goals
Keywords: Energy; Economics